ANALISIS PEMASARAN SAPI BALI DI KECAMATAN BANTAENG KABUPATEN BANTAENG - Astati Astati (Teknosains, 2015)
The aim of this research was to know margin and efficiency of marketing Bali cattle at Bantaeng district Bantaeng regency. The research was done during 2 (two) mounth commencing from March up to April 2014. Data were collected using observation and interview method. Operational is breeder, Bali cattle trader, traders, wholesalers, butcher, retailers, consumer, margin of marketing Bali cattle, channels of marketing Bali cattle, and efficiency of marketing Bali cattle. Margin of marketing Bali cattle at marketing agency showed different from traders, wholesalers, butcher, and retailers. Efficiency of marketing Bali cattle showed efficient is EP < 1..